Hypothesis On The Source, Transmission and Characteristics of Infection of Avian Influenza A (H7N9) Virus – Based On Analysis of Field Epidemiological Investigation and Gene Sequence Analysis. (13th March 2014) - Ling, F.; Chen, E.; Liu, Q.; Miao, Z.; Gong, Z.
Summary On 31 March 2013, the National Health and Family Planning Commission announced that human infections with influenza A (H7N9) virus had occurred in Shanghai and Anhui provinces, China. H7N9 cases were later detected in Jiangsu and Zhejiang provinces. It was estimated that the virus first spread northward along the route taken by migratory birds and then spread to neighbouring provinces with the sale of poultry. Epidemiological studies were carried out on samples from the external environment of infected cases, transmission routes, farmers markets and live poultry markets. Phylogenetic study of viral sequences from human and avian infections in Zhejiang showed that those from Shanghai and Jiangsu provinces along Taihu Lake were highly homologous with those from the external environment. This suggests that avian viruses carried by waterfowl combined with the virus carried by migratory birds, giving rise to avian influenza virus H7N9, which is highly pathogenic to humans. It is possible that the virus was transmitted by local wildfowl to domestic poultry and then to humans, or spread further by means of trading in wholesale poultry markets. As the weather has turned warm, and with measures adopted to terminate poultry trade and facilitate health communication, the epidemic in the first half of the year has been kept under control. However, the infection source in the triangular area around Taihu Lake still remains. The H7N9 epidemic will probably hit the area later in the year and next spring when the migratory birds return and may even spread to other areas. Great importance should therefore be attached to the wildfowl in Taihu Lake as the repository and disseminator of the virus: investigation and study of this population is essential.